A Nanochemist and a Nanohumanist Take a Walk Through the German Museum: An Analysis of the Popularization of Nanoscience and Technology in Germany. Issue 1 (21st July 2014) - Youngman, Paul A; Fruk, Ljiljana
This paper is an analysis of the NST (Nanoscience and Technology) exhibit at the DM (Deutsches Museum) from the point of view of a German studies scholar and a nanoscientist. Established in 2005, the exhibit and its associated lectures, tours, and documentation purport to make the public more familiar with the new technology and its applications. Our task was to evaluate the science as it is presented and, equally importantly, the story the museum tells about NST, since science can never be isolated from its cultural narrative; it can never be culled from the culture in which it is embedded despite our penchant for a neat division between these two realms. By evaluating the science as it is presented in the museum and considering it within its German cultural context, we offer an analytical overview of NST in the public sphere. Secondly, we cast our eye toward discerning the 'why' of the exhibit. Is it designed to civilize and enlighten and thus empower the public in their understanding of NST as an emerging technology? Does the exhibit have a propagandistic aspect designed to sway the public in hope of avoiding the difficult struggles that have embroiled emergent technologies in the past? Or, is the nanoexhibit a hybrid of each approach intended to both enlighten and sway?